Quality assessment of sputum for Acid Fast Bacilli(AFB) test in microbiology laboratories before and after implementation of Standard Operating Procedure (SOP): a comparative study - Khadeza, K; Kamal, AHM; Naima, M; Shamsuzzaman, SM (Bangladesh Journal of Medical Science, 2012)
Aims: To evaluate the present status of microbiology laboratory by comparing the test results of investigator with that of laboratory staff for sputum for Acid Fast Bacilli (AFB) withZiehl-NeelsenStaining (Z-N Staining) at primary and secondary level andto assess the present status of a microbiology laboratory for sputum for Acid Fast Bacilli (AFB) withZiehl-NeelsenStaining (Z-N Staining) at tertiary level. Material and Methods: Type of study : Cross sectional, descriptive type of study. Place of study: Department of Microbiology of Dhaka Medical College,Narsingdi Sadar Hospital,Narsingdi,PolashUpzilla Health Complex ,Polash, Narsingdi andDOTS centers. Duration of study: From July, 2007 to June,2008 Method of sampling: Non probability, purposive and convenient sampling Sample Size: Sputum for AFB: 300 sputum samples were collected for detection of AFB by direct Z-N staining, Z-N staining after bleach centrifugation and Auramine phenol staining before implementing SOP. After following SOP 150 sputum samples were collected and tested in direct Z-N method. Results: In the present study, before SOP out of 100 sputum smear at each level, discrepancy was found in 3% cases at primary level, 2% cases at secondary level and 1% case at tertiary level.After following SOP out of 50 sputum smear at each level, discrepancy was reduced to 2% cases at primary level and no discrepancy was found at secondary and tertiary level. Conclusion: Each laboratory must have SOP for laboratory testing to set the minimum acceptable standard for every test in order to improve and maintain the quality of laboratory services. DOI: http://dx.doi.org/10.3329/bjms.v11i1.9824 BJMS 2012; 11(1): 51-56